Software in the scientific literature: Problems with seeing, finding, and using software mentioned in the biology literature. - Howison, James; Bullard, Julia (Journal of the Association for Information Science & Technology, 2016)
Software is increasingly crucial to scholarship, yet the visibility and usefulness of software in the scientific record are in question. Just as with data, the visibility of software in publications is related to incentives to share software in reusable ways, and so promote efficient science. In this article, we examine software in publications through content analysis of a random sample of 90 biology articles. We develop a coding scheme to identify software 'mentions' and classify them according to their characteristics and ability to realize the functions of citations. Overall, we find diverse and problematic practices: Only between 31% and 43% of mentions involve formal citations; informal mentions are very common, even in high impact factor journals and across different kinds of software. Software is frequently inaccessible (15%-29% of packages in any form; between 90% and 98% of specific versions; only between 24%-40% provide source code). Cites to publications are particularly poor at providing version information, whereas informal mentions are particularly poor at providing crediting information. We provide recommendations to improve the practice of software citation, highlighting recent nascent efforts. Software plays an increasingly great role in scientific practice; it deserves a clear and useful place in scholarly communication.